The trends of burns epidemiology in a tropical regional burns centre. Issue 3 (May 2016) - Hwee, Jolie; Song, Christopher; Tan, Kok Chai; Tan, Bien Keem; Chong, Si Jack
Highlights: 655 cases over a 3-year-period in a tropical regional burns centre. Burns ≥20% total body surface area (TBSA) have a higher risk of bacteremia. TBSA ≥34% TBSA is a predictor of mortality. Operations ≥80 min correlate with a higher incidence of burns infection. Key factors of mortality include inhalational injury, bacteremia and ≥34% TBSA. Abstract: Introduction: Singapore General Hospital (SGH) is a regional burns centre in Southeast Asia and is the only dedicated burns facility providing specialized burns care in Singapore. Methods: A cohort study was performed for burns patients admitted to SGH from 2011 to 2013. We compared our data with earlier studies and observed the trends of burns epidemiology in Singapore. Results were analyzed using the SPSS programme. Results: 655 patients were admitted during this study period, a 35.9% increase from 2003 to 2005. Scalding by water and flame injury remain the top causes of burns and the mean extent of burn is 9.5%. TBSA correlates with the incidence of burn infection, bacteremia and mortality. Patients with ≥20% TBSA are at a higher risk of bacteremia, and ≥ 34% TBSA is a predictor of mortality. 4.9% ( n = 32) of our patients developed bacteremia. Bacteremia was associated with a surgical duration of ≥80 min. Patients with bacteremia incurred longer hospitalization, and had higher mortality rates. Overall mortality rate of our burns patients has decreased from 4.5% to 2.7% ( n = 18). Key factors of mortality include inhalational injury, bacteremia and ≥20% TBSA. Conclusion: This is a large epidemiology study of a tropical region burns centre. A total of 655 burns cases over a 3-year period were analyzed. We analysed the key factors associated with adverse outcomes including burns infection, bacteremia and mortality, factors associated with mortality, and discussed strategies on the optimization of burns care.